A single tumour necrosis factor haplotype influences the response to adalimumab in rheumatoid arthritis. Issue 4 (2nd August 2007) - Miceli-Richard, C; Comets, E; Verstuyft, C; Tamouza, R; Loiseau, P; Ravaud, P; Kupper, H; Becquemont, L; Charron, D; Mariette, X
Abstract : Objective: To determine whether tumour necrosis factor ( TNF ) gene polymorphisms and/or the shared epitope are genetic predictors of the response to adalimumab (ADA) in rheumatoid arthritis (RA). Methods: This ancillary study to the Research in Active Rheumatoid Arthritis (ReAct) Phase IIIb study included a large cohort of Caucasian patients with RA from France (n = 388) treated with ADA plus methotrexate (MTX) (n = 182), ADA plus any other DMARD (n = 98) or ADA alone (n = 108). The primary outcome was ACR50 at 12 weeks. Patients underwent genotyping for HLA-DRB1 and three TNF gene polymorphisms (–238A/G, –308A/G and–857C/T). Extended haplotypes involving HLA-DRB1 and TNF loci were reconstructed using the PHASE program. Results: A total of 151 patients (40%) had an ACR50 response at week 12. Neither the number of HLA-DRB1 shared epitope copies nor presence of the three TNF polymorphisms tested separately was significantly associated with ACR50 response at week 12. However, haplotype reconstruction of the TNF locus revealed that the GGC haplotype (–238G/–308G/–857C) in a homozygous form (i.e. present in more than half of the patients) was significantly associated with a lower ACR50 response to ADA at 12 weeks (34% vs. 50% in patients without the haplotype) (p = 0.003; pa = 0.015). This effect was more important in the subgroup of patients concomitantly treated with MTX. Conclusion: This large pharmacogenetic study provides preliminary data indicating that a single TNF locus haplotype (–238G/–308G/–857C), present on both chromosomes is associated with a lower response to ADA, mainly in patients treated with ADA and MTX.